OLIY TA’LIM MUASSASASI TALABALARINI KOMUNIKATIV KOMPETENTLIGINI RIVOJLANTIRISH - Sulaymonov , Abdulhamid Xolbo‘ta o‘g‘li (Educational Research in Universal Sciences, 2023)
This article presents ideas about competence, issues of developing students’ communicative competence, types of competence.